2022
DOI: 10.1097/icl.0000000000000916
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Omega-3 on HLA-DR Expression by Conjunctival Cells and Tear Cytokine Concentrations in the Dry Eye Assessment and Management Study

Abstract: Objectives: To determine effect of omega-3 supplementation on conjunctival cell HLA-DR expression and tear concentrations of interleukin (IL)-1b, IL-6, IL-8, IL-10, IL-17A, interferon-g, and tumor necrosis factor-a in dry eye disease patients in the Dry Eye Assessment and Management study. Methods: Patients were randomized to receive a daily dose of eicosapentaenoic and docosahexaenoic acids (v3) or refined olive oil (placebo) for 12 months. At baseline, 6 and 12 months, HLA-DR expression in conjunctival total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Additional parameters, such as tear film break-up time (BUT), Schirmer's Test, corneal examination using fluorescein (following the National Eye Institute [NEI] protocol), and conjunctival staining with lysamine green (according to NEI), among others, were also assessed and compared. However, the results after one year of omega-3 fatty acids and placebo showed no statistically significant difference between the groups, indicating a lack of efficacy of omega-3 fatty acids as an adjunctive treatment for dry eye syndrome [2,8,[15][16][17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…Additional parameters, such as tear film break-up time (BUT), Schirmer's Test, corneal examination using fluorescein (following the National Eye Institute [NEI] protocol), and conjunctival staining with lysamine green (according to NEI), among others, were also assessed and compared. However, the results after one year of omega-3 fatty acids and placebo showed no statistically significant difference between the groups, indicating a lack of efficacy of omega-3 fatty acids as an adjunctive treatment for dry eye syndrome [2,8,[15][16][17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…The latter, in turn, preserves homeostasis of the ocular surface epithelium and protects it from physical damage and exposure (Kawakita, 2018). Dysfunction of one or more components of the LFU 1) hinders the composition of tears, and thus its ability to protect the surface epithelium; 2) disrupts the innate and adaptive immune and inflammatory pathways that protect the ocular surface from external stimuli (i.e., exposure, infection); and 3) stimulate the production of proinflammatory cytokines [i.e., interferon (IFN)-γ, interleukin (IL)-1, −6, −8, tumor necrosis factor (TNF)-α, intercellular adhesion molecule (ICAM)-1, among others] by the ocular surface immune and epithelial cells (Roy et al, 2022).…”
Section: Nitric Oxide (No)-donating Prostaglandin Analogs (Pgas)mentioning
confidence: 99%
“…[ 8 - 10 ] It has also led to the identification of specific inflammatory factors, which can act as biomarkers for DED[ 11 - 13 ] as well as targets for appropriate management of the progression of ocular surface damage. [ 2 , 14 , 15 ] Because different studies use different approaches and represent different ethnic groups and etiologies, it is imperative to collate recent studies pertaining to the measurement of soluble factor levels in tears of dry eye patients as it is important not only to understand and reach consensus on key molecular factors driving the disease but also to identify plausible biomarkers for point of care kit development for use in clinics. This study thus focuses on discussing the molecular factors that have been reported in various studies in the last decade and understanding the significance of these factors in disease pathophysiology.…”
mentioning
confidence: 99%